Recognition of out-of-hospital cardiac arrest by medical dispatchers in emergency medical dispatch centres in two countries. (December 2016) - Møller, Thea Palsgaard; Andréll, Cecilia; Viereck, Søren; Todorova, Lizbet; Friberg, Hans; Lippert, Freddy K.
Abstract: Introduction: Survival after out-of-hospital cardiac arrest (OHCA) remains low. Early recognition by emergency medical dispatchers is essential for an effective chain of actions, leading to early cardiopulmonary resuscitation, use of an automated external defibrillator and rapid dispatching of the emergency medical services. Aim: To analyse and compare the accuracy of OHCA recognition by medical dispatchers in two countries. Method: An observational register-based study collecting data from national cardiac arrest registers in Denmark and Sweden during a six-month period in 2013. Data were analysed in two steps; registry data were merged with electronically registered emergency call data from the emergency medical dispatch centres in the two regions. Cases with missing or non-OHCA dispatch codes were analysed further by auditing emergency call recordings using a uniform data collection template. Results: The sensitivity for recognition of OHCA was 40.9% (95% CI: 37.1–44.7%) in the Capital Region of Denmark and 78.4% (95% CI: 73.2–83.0%) in the Skåne Region in Sweden (p < 0.001). With additional data from the emergency call recordings, the sensitivity was 80.7% (95% CI: 77.7–84.3%) and 86.0% (95% CI: 81.3–89.8%) for the two regions (p = 0.06). The majority of the non-recognised OHCA were dispatched with the highest priority. Conclusion: The accuracy of OHCA recognition was high and comparable. We identified large differences in data registration practices despite the use of similar dispatch tools. This raises a discussion of definitions and transparency in general in scientific reporting of OHCA recognition, which is essential if used as quality indicator in emergency medical services